Temporal Gene Expression Profiles of Pre Blood-Fed Adult Females Immediately Following Eclosion in the Southern House Mosquito Culex Quinquefasciatus - Reid, William R. (Int J Biol Sci, 2015)
Prior to acquisition of the first host blood meal, the anautogenous mosquito Culex quinquefasciatus requires a period of time in order to prepare for the blood feeding and, later, vitellogenesis. In the current study, we conducted whole transcriptome analyses of adult female Culex mosquitoes to identify genes that may be necessary for both taking of the blood meal, and processing of the blood meal in adult female mosquitoes Cx. quinquefasciatus. We examined temporal expression of genes for the periods of post eclosion and prior to the female freely taking a blood meal. We further evaluated the temporal expression of certain genes for the periods after the taking of a blood meal to identify genes that may be necessary for both the taking of the blood meal, and the processing of the blood meal. We found that adult females required a minimum of 48 h post-eclosion before they freely took their first blood meal. We hypothesized that gene expression signatures were altered in the mosquitoes before blood feeding in preparation for the acquisition of the blood meal through changes in multiple gene expression. To identify the genes involved in the acquisition of blood feeding, we quantified the gene expression levels of adult female Cx. quinquefasciatus using RNA Seq throughout a pre-blooding period from 2 to 72 h post eclosion at 12 h intervals. A total of 325 genes were determined to be differentially-expressed throughout the pre-blooding period, with the majority of differentially-expressed genes occurring between the 2 h and 12 h post-eclosion time points. Among the up-regulated genes were salivary proteins, cytochrome P450s, odorant-binding proteins, and proteases, while the majority of the down-regulated genes were hypothetical or cuticular genes. In addition, Trypsin was found to be up-regulated immediately following blood feeding, while trypsin and chymotrypsin were up-regulated at 48h and 60h post blood-feeding, respectively, suggesting that these proteases are likely involved in the digestion of the blood meal. Overall, this study reviewed multiple genes that might be involved in the adult female competency for blood meal acquisition in mosquitoes.